Production cost and market analysis of mandarin in Dhading District of Nepal - Shrestha, D (Journal of Agriculture and Environment, 2015)
A study was conducted in 2010 to explore the value chain of the mandarin business in two VDCs; Nalang and Jogimara of Dhading district, Nepal. Information were collected through survey from 60 mandarin growers, 4 collectors, 2 agroinput traders, 2 fruit nurseries, 4 technical service providers, 4 dealers, 4 wholesalers, 4 retailers and 20 consumers. Different direct actors and organizations were found to be involved in micro, meso and macro levels of the mandarin value chain. The technical structure of the mandarin value chain was found as the input provision, mandarin production, intermediary trading, retailing, and consumption. The value chain was linked to different regions of the country. On an average, mandarin producers incurred total variable cost of NRs 10.40 per kg of mandarin. Their gross margin was NRs 8.44 per kg of mandarin. The cost of marketing of the traders, wholesalers, and retailers were NRs 3.56, 5.38 and 1.98 per kg of mandarin respectively whereas the margins of each of them were NRs 2.54, 2.36 and 5.01 per kg of mandarin respectively. The role of traders was found dominant in both purchasing of mandarin from producers and supplying to other districts. The majority of producers were not getting adequate training, support and supervision from concerned organizations. The major weakness in mandarin value chain was unorganized marketing system. Intermediaries and retailers were always found to be in profit. Therefore, the concerned organizations should bring policies in fixing the market price of mandarin based on cost of production. An upgrading strategy with the technology based processed mandarin production has a great opportunity to enter in the new value chain for further improvements in the existing mandarin business.